2023
DOI: 10.3390/jcm12052083
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Disorders after Surgical Aortic Valve Replacement Using a Rapid Deployment Aortic Valve Prosthesis: Medium-Term Follow-Up

Abstract: Background: We have previously reported that the incidence of postoperative conduction disorders, especially left bundle branch block (LBBB), after implantation of a rapid deployment Intuity™ Elite aortic valve prosthesis (Edwards Lifesciences, Irvine, CA, USA), was significantly increased compared with conventional aortic valve replacement. We were now interested in how these disorders behaved at intermediate follow-up. Methods: All 87 patients who had undergone surgical aortic valve replacement (SAVR) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…After commercialization of the INTUITY device, several institutions have shown a lower rate of PPM with increased experience and enhanced technique. 17 , 18 A follow-up study revealed only a single new PPI in 87 patients at risk over the 2 years of monitoring, for a cumulative rate of 10.1%. 18 This is in alignment with the reported 2-year cumulative PPI rates of 9.1% for transcatheter AVR and 7.0% for surgical AVR in the PARTNER 3 study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After commercialization of the INTUITY device, several institutions have shown a lower rate of PPM with increased experience and enhanced technique. 17 , 18 A follow-up study revealed only a single new PPI in 87 patients at risk over the 2 years of monitoring, for a cumulative rate of 10.1%. 18 This is in alignment with the reported 2-year cumulative PPI rates of 9.1% for transcatheter AVR and 7.0% for surgical AVR in the PARTNER 3 study.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 A follow-up study revealed only a single new PPI in 87 patients at risk over the 2 years of monitoring, for a cumulative rate of 10.1%. 18 This is in alignment with the reported 2-year cumulative PPI rates of 9.1% for transcatheter AVR and 7.0% for surgical AVR in the PARTNER 3 study. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Several shortcomings of Intuity valve reported in the previous studies should be recognized. The number of new postoperative conduction disorders, especially left bundle branch block, remains high during follow-up, although the long-term clinical significance was undetermined ( 31 ). There are also concerns that the existence of the subvalvular structure might cause anatomical changes in the aortic-mitral fibrous continuity, thus resulting in the alteration of mitral annular motion ( 32 ).…”
Section: Discussionmentioning
confidence: 99%